Light‐Tunable Nonvolatile Memory Characteristics in Photochromic RRAM. (4th July 2017) - Ling, Haifeng; Tan, Kangming; Fang, Qiyun; Xu, Xinshui; Chen, Hao; Li, Wenwen; Liu, Yefan; Wang, Laiyuan; Yi, Mingdong; Huang, Ru; Qian, Yan; Xie, Linghai; et al.
Abstract : Light‐tunable resistive switching (RS) characteristics are demonstrated in a photochromophore (BMThCE)‐based resistive random access memory. Triggered by nondestructive ultraviolet or visible light irradiation, two memory‐type RS characteristics can be reversibly modulated in the same device upon a narrow range of applied voltage (<6 V), accompanied by the photochromophores in the active layer reversibly changed between ring‐open state (namely, o ‐BMThCE) and ring‐closed state (namely, c ‐BMThCE). The o ‐BMThCE‐based memory exhibits a write‐once‐read‐many characteristic with a high current on/off ratio of 10 5, while the c ‐BMThCE‐based one shows a flash characteristic. Both of the RS characteristics present good nonvolatile stability with the resistance states maintained over 10 4 s without variation. This RS modulation is possibly related to the formation and rupture of conductive filaments, which formed along channels consisting of BMThCE trapping molecules. This work provides a new memory element for the design of light‐controllable high density storage and data encryption technology. Abstract : Light‐tunable nonvolatile memory characteristics are demonstrated in a single photochromophore‐based resistive random access memory. Trigged by ultraviolet or visible light irradiation, write‐once‐read‐many, and flash memories can be reversibly modulated (<6 V). The origin of this resistive switching modulation is related to the rupture and reformation of conductive filaments, along channels consisting of charge‐filled photochromic trapping molecules.